Role of the Barrier Dysfunction of the Intestines in the Development of Alimentary Allergy in Children - T. E. Borovik; S. G. Makarova; G. V. Yatsyk; T. N. Stepanova; S. G. Gribakin (Вопросы современной педиатрии, 2013)
Intestinal epithelial barrier plays an important role in prevention of bacterial translocation and food allergens penetration. Article is dedicated to intestinal epithelial barrier disfunctions leading to sensitization. Special attention is paid to molecular mechanisms increasing the allergens penetration through intestinal wall. Phase of sensitization is characterized by antigen-induced crossover IgE connection with FcRI receptor on the surface of mast cell which leads to anaphylactic reaction.Key words: infants, food allergy, sensitization, intestinal epithelial barrier.